THE EFFECTS OF RELİGİOUS BELİEFS ON INSURANCE DEMAND: A PHENOMENOLOGİCAL RESEARCH (Third Sector Social Economic Review, 2020)
This study focused on researching and understanding the relationship between religious beliefs and insurance claim. In the study, the relationship between religious beliefs and insurance claim was investigated. In this context, insurance-related attitudes and behaviors of conservative groups living in Turkey were examined in depth. In line with this purpose, important findings were obtained as a result of interviews with 7 imams working in different districts of Ankara. The first of these is that, in the fatwa published by the Ministry of Religious Affairs, it is emphasized that insurance is not haram and that it is permissible, but the majority of the participants contradict with religion as a personal opinion. They define insurance as a gambling, interestism and the probability of profit arising from uncertainty. According to other participants, insurance was expressed as one of the forms of implementation in which the concept of solidarity, which is at the core of Islam, has found a place in the modern world. However, they also emphasized that the insurance should be purified from interest and should be in the form of participation.
Keywords: Insurance Demand; Culture; Religious